Fibroid with unilateral streak ovary in Mullerian Agenesis! A rare case report - Malik, Renuka; Goyal, Avani; Bhardawaj, Meenakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Mayer-Rokitansky-Kuster-Hauser (MRKH) syndrome is a rare anomaly (1/5000) associated with uterine and vaginal aplasia with normal ovaries. A fibroid in a normal uterus is common but a fibroid arising from rudimentary horn in Mayer-Rokitansky-Kuster-Hauser (MRKH) syndrome is very rare. It is also rare to have the association of unilateral ovarian dysgenesis in MRKH. A 37 year old married female with primary amenorrhea presented to the OPD of Dr. RML Hospital with abdominopelvic mass for one year. She was phenotypically normal looking and there was no other associated cardiac, ocular or skeletal abnormality. A large 15 × 15 cm abdominopelvic mass was present in suprapubic area which was firm in consistency and non-tender. A Two and a half inch long blind vaginal pouch was present with absence of cervix and uterus. A provisional diagnosis of solid ovarian tumor in MRKH syndrome was made. Her investigations -Serum FSH, LH, estradiol and tumor markers were normal. Her ultrasound and MRI reported a fibroid with normal ovaries. Laparotomy revealed absence of uterus and cervix and a large fibroid arising from right rudimentary horn with left streak ovary. Right ovary was enlarged to 4 × 4 cm, showing multiple small follicles. Fibroid along with the rudimentary horns and the streak ovary was removed, preserving the normal right ovary. Histopathology confirmed the diagnosis of leiomyoma in rudimentary horn with left streak ovary, making it class1 type b anomaly under American fertility society classification. Preoperative assessment of rare anomalies can be different from intraoperative findings in certain female reproductive tract anomalies. Awareness of rare combinations can help in judicious management of such cases.